Grand Theatre, Oratory and Anthropology in the Documentaries of Andrzej Fidyk - Fiołek-Lubczyńska, Bogumiła (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
The article centres on the documentary works of Andrzej Fidyk. The director is fascinated by cultural anthropology. Showing diff erent aspects of social life in a theatrical manner is an omnipresent motif in his movies. A fi lm in general, by its nature, is a spectacle, but the director depicts within its reality diff erent kinds of spectacles: parades, as in the title of Th e Parade, musical scenes in Yodok Stories, and carnival in Carnaval…. Th e crown jewel in this double, increasing spectacularity is Carnaval. Th e Biggest Party In Th e World, and the movie inside the movie – Cameramen from Calcutta. A religious spectacle can be found inside Staszek’s Dream abstracts314 in Teheran. Scenes of muslim grief three years aft er the death of Chomeini, inside a country considered to be exemplary in its religiousness are compared to “the trend of going to orthodox churches” in Russia. Th e most interesting by the criteria of spectacularity is Carnaval…, which has been the subject of many analysis and interpretations by cultural theorists, anthropologists and sociologists. Fidyk in his movie shows the nature of this spectacle with great fi nery.